Validation of the World Health Organization Disability Assessment Schedule (WHO-DAS II) in Greek and its added value to the Short Form 36 (SF-36) in a sample of people with or without disabilities - Xenouli, Georgia; Xenoulis, Kostis; Sarafis, Pavlos; Niakas, Dimitris; Alexopoulos, Evangelos C. (My University, 2016)
There is controversy and ongoing interest on the measurement of functionality in the personal and social level.
Keywords: Disability; Functionality; Mental health; Perceived stress; Physical health